The Impact of Lens Vault on Visual Acuity and Refractive Error: Implications for Management of Primary Angle-closure Glaucoma. Issue 3 (March 2016) - Nongpiur, Monisha E.; Singhal, Shweta; Stewart, Stephen; Htoon, Hla M.; Narayanaswamy, Arun K.; Wong, Tien Y.; Perera, Shamira A.; Aung, Tin
Abstract : Purpose: To investigate the relationship between lens vault (LV), visual acuity (VA), and refraction. Methods: This was a cross-sectional study of 2047 subjects aged 50 years and older recruited from a community polyclinic. Anterior segment optical coherence tomography was performed, and customized software was used to measure LV. VA was measured using a logarithm of minimum angle of resolution chart (logMAR chart; Lighthouse Inc.), and was classified as normal (logMAR<0.3), mild impairment (0.3<logMAR<0.6), and moderate/severe impairment (logMAR>0.6). Refraction was measured with an autorefractor machine and spherical equivalent was defined as sphere plus half cylinder. Angle closure was defined as posterior trabecular meshwork not visible for ≥2 quadrants on nonindentation gonioscopy. Results: Complete data were available for 1372 subjects including 295 (21.5%) with angle closure. Angle-closure subjects were significantly older ( P <0.001), with shorter axial length ( P <0.001), shallower anterior chamber depth ( P <0.001), and greater LV ( P <0.001). There was no significant difference in VA ( P =0.12) compared with those without angle closure. After adjusting for age, sex, axial length, anterior chamber depth, and spherical equivalent, there was no significant association between LV and VA ( P =0.35) or between LV and spherical equivalent ( P =0.06). Conclusions: The magnitude of LV was not associated with VA or spherical equivalent. Lens extraction may be a consideration in eyes with angle closure with large LV in the absence of visually significant cataract.